Identifikasi Jamur C. albicans pada Urine Penderita Diabetes Melitus di Griya Sehat Link Care Kabupaten Bulukumba: Identification of C. albicans in the Urine of Diabetes Mellitus Patients at Griya Sehat Link Care, Bulukumba Regency - Dzikra Arwie; Sarmila Sarmila; Asriyani Ridwan; Rahmat Aryandi; Islawati Islawati (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia, or blood sugar levels higher than normal. This condition is one of the major risk factors for the development of C. albicans, a fungal pathogen commonly found in tropical countries. Infections caused by C. albicans in diabetes mellitus patients can lead to serious complications, including severe sepsis, if left untreated. This study aims to identify the presence of C. albicans in the urine of diabetes mellitus patients at Griya Sehat Link Care, Bulukumba Regency. A descriptive study design was employed, with random sampling of 15 respondents. Analysis was performed using the Sabouraud Dextrose Agar (SDA) method, and results were presented in tabular distribution format. The findings revealed that five respondents (33.3%) tested positive for C. albicans in their urine samples, while ten respondents (66.7%) tested negative. These results emphasize the importance of early detection of C. albicans infection in diabetes mellitus patients to prevent further complications. Additionally, this study provides a reference for developing prevention and management protocols for fungal infections in diabetic patients, particularly in tropical regions like Indonesia. Keywords: C. albicans; Early detection; Diabetes mellitus; Fungal infection; Urine.